SYN- TO POST-KINEMATIC FIBROLITE-BIOTITE INTERGROWTHS IN THE ARDARA AUREOLE, NW IRELAND (Journal of Sciences, Islamic Republic of Iran)
The relations of fibrolite-biotite are discussed by presenting data from the Ardara aureole, NW Ireland. Biotite-fibrolite intergrowths are developed in all three aureole zones including: the outer kyanite-bearing andalusite zone, the middle kyanite-free andalusite zone and the inner prismatic sillimanite zone. A strain-assisted mechanism is proposed for the fibrolitisation of biotite in the Ardara aureole. The concentration of fibrolite in zones of high non-coaxial strain, which wrap around zones of low co-axial strain, now occupied by minerals such as plagioclase (in the outer kyanite-bearing andalusite zone), andalusite (in the middle kyanite-free andalusite zone) and pods rich in biotite, quartz and plagioclase (in the inner sillimanite zone) provides strong evidence that fibrolite growth was syn-kinematic. Some textural evidence, especially from the inner sillimanite zone is consistent with continuation of fibrolite growth after ductile deformation.